PENGARUH PEMBERIAN TEH HITAM (Camellia sinensis) TERHADAP GAMBARAN HISTOPATOLOGI ARTERI KORONARIA TIKUS PUTIH GALUR WISTAR YANG DIINDUKSI MINYAK JELANTAH - Yovani Rehuel Br Sitepu; Rizki Hanriko; Ari Wahyuni (Majority, 2023)
Used cooking oil contains free radicals and free fatty acids which can cause damage to the coronary artery. Black tea contains flavonoids and theaflavins are antioxidants that can prevent coronary artery damage. This study aims to determine the effect of giving black tea (Camellia sinensis) on the coronary artery histopathology of Wistar white rats induced by used cooking oil. This study used a Post-test Control Group Design pattern using 25 rats which were divided into 5 groups with 28 days of treatment. The group K- was given 2 ml distilled water. The group K+ was given used cooking oil 1,5 ml/day. The group P1 was given used cooking oil of 1,5 ml/day and black tea 15 mg/day. The group P2 was given used cooking oil of 1,5 ml/day and black tea 30 mg/day. The group P3 was given used cooking oil 1.5 ml/day and black tea 45 mg/day. Observations were made using a microscope by looking at the circumference of the lumen diameter. The results of the mean coronary artery lumen diameter of the rats at K-=116,21±13,17 μm; K+=69,25±7,74 μm; P1=90,72±9,58 μm; P2=102,89±17,69 μm; and P3=125,06±9,67μm. This study used the one-way ANOVA parametric test (p<0,05) and continued with the post-hoc LSD test (p<0,05). There is an effect of giving black tea (Camellia sinensis) on the coronary artery histopathology of Wistar white rats induced by used cooking oil.